2017
DOI: 10.1155/2017/6453420
|View full text |Cite
|
Sign up to set email alerts
|

Status of Biomass Derived Carbon Materials for Supercapacitor Application

Abstract: Environmental concerns and energy security uncertainties associated with fossil fuels have driven the world to shift to renewable energy sources. However, most renewable energy sources with exception of hydropower are intermittent in nature and thus need storage systems. Amongst various storage systems, supercapacitors are the promising candidates for energy storage not only in renewable energies but also in hybrid vehicles and portable devices due to their high power density. Supercapacitor electrodes are alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 123 publications
0
36
0
Order By: Relevance
“…CV curves for Chem-900-2 at different scan rates from 5t o1 00 mV s À1 show no noticeable peaks andi ndicate ar apid and efficient charge transfer and ac harge/dischargep rocess typical for an electrical double layer capacitor ( Figure 1b). All in all, the Chem-900-2 sample demonstrates an electrochemical performance close to (or higher than) the performances of typical bio-waste derived ACs studied in aqueous KOH electrolyte, [46][47][48] although the SSA of Chem-900-2i su pt oa pproximately four times lower than the SSAs of other carbon materials described in the literature. SEM and TEM studies of the electrode active mass before and after GCD cycling revealed no significant changes of the porouss tructure of the carbon material (Figures S10 and S11).…”
Section: Electrochemical Experiments In Athree-electrode Systemmentioning
confidence: 99%
“…CV curves for Chem-900-2 at different scan rates from 5t o1 00 mV s À1 show no noticeable peaks andi ndicate ar apid and efficient charge transfer and ac harge/dischargep rocess typical for an electrical double layer capacitor ( Figure 1b). All in all, the Chem-900-2 sample demonstrates an electrochemical performance close to (or higher than) the performances of typical bio-waste derived ACs studied in aqueous KOH electrolyte, [46][47][48] although the SSA of Chem-900-2i su pt oa pproximately four times lower than the SSAs of other carbon materials described in the literature. SEM and TEM studies of the electrode active mass before and after GCD cycling revealed no significant changes of the porouss tructure of the carbon material (Figures S10 and S11).…”
Section: Electrochemical Experiments In Athree-electrode Systemmentioning
confidence: 99%
“…Global energy consumption has been accelerating at an alarming rate due to the rapid development of the global economy and the growing human population worldwide [1][2][3][4][5][6][7][8][9]. To meet the growing energy demands required to sustain current living standards while avoiding depletion and environmental pollution, there is a need for the development of high-performance, low-cost and environment-friendly energy resources.…”
Section: Introductionmentioning
confidence: 99%
“…In order to be able to use these environmentally friendly and renewable sources of energy in the long term, new and effective energy storage systems must be developed [10]. Supercapacitors (also known as electrochemical capacitors or ultracapacitors) are a type of energy storage device that is attracting more and more attention because they can be charged and discharged C 2020, 6, 17; doi:10.3390/c6020017 www.mdpi.com/journal/carbon C 2020, 6, 17 2 of 12 very fast, have a very high power density (<10,000 W•kg −1 ), require little maintenance and have a long life of over 1 million charge and discharge cycles [1,2,11]. For the production of such supercapacitors, carbon materials are used as electrodes, since they are chemically and thermally stable and easy to process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various chemical activating agent can be used in chemical activation process, such as ZnCl 2 , KOH, H 2 SO 4 , H 3 PO 4 , HNO 3 , etc. [10]. Recently, various types of raw material, chemical activating agent, and physical activation method in the making process of activated carbon are studied [11][12][13].…”
Section: Introductionmentioning
confidence: 99%